Impact of Covid-19 pandemic on urology practice in tertiary hospital in Banda Aceh, Indonesia: a descriptive study - Kiagus Ferry Fabian Qosasi; Dahril (Journal of International Surgery and Clinical Medicine, 2021)
ABSTRACT Introduction: Coronavirus disease-19 (Covid-19) pandemic has brought a dramatic change in health care worldwide, including urologic care. Patients requiring non-covid care are encouraged to avoid hospital visits and postpone elective surgeries to reduce the risk of transmission and anticipate a surge in Covid-19 patients. This study aims to describe Covid-19-related changes in urologic care in tertiary hospitals in Banda Aceh, Indonesia.  Methods: This is a descriptive study in dr. Zainoel Abidin Regional General Hospital, Banda Aceh. The number of outpatients’ visits and urologic surgeries performed in March – October 2020 were recorded and compared to the numbers within the same period in 2019. The most common surgery performed during a pandemic is determined.  Results: The number of outpatient visits in March – October 2020 was 2,595 visits, while in 2019 was 3,886. There was a 54.29% decrease in March-May 2020 and a 17.76% decrease in June – October 2020. The number of surgeries carried out in March – October 2020 was 381, while in 2019 was 264. The most common surgeries performed during the pandemic is stones removal (n = 119) and reconstructive surgeries (n = 104).  Conclusion: There were decreases in both number of outpatients’ visits and surgeries performed during the Covid-19 pandemic. The most common urologic surgery carried out during the pandemic were stones removal and reconstructive surgeries.